The “Double Minority”: An interpretive phenomenological analysis of engineering education culture and intersectionality for women of colour studying Engineering at Swansea University - JENNIE WATKINS (2023)
Women of colour remain underrepresented in engineering despite decades of interventions. Workforce statistics in the UK show only 2% of all engineering professionals are women of colour. Several studies, predominantly in the United States, have explored the impact gender and race have in engineering education and the “leaky pipeline” to employment in the sector; however, to date limited examination of the phenomenon of intersectionality using qualitative methods has occurred in UK higher education institution. Therefore, the aim of the present study was to explore the experiences of women of colour studying engineering education at Swansea University to consider implications for institutional policy and strategy for the enhancement of student experience and academic practice. Specifically, through this study the aim was to provide a voice to the women of colour studying engineering courses at Swansea University, and to consider the impact of engineering culture on race and gender, or intersectionality, as the ‘double minority’ in engineering education.This study was conducted using Interpretive Phenomenological Analysis. Interviews were conducted with five international undergraduate students, identifying as international women of colour studying engineering. Further, five appointed student representatives and staff were recruited to provide insight and experience relating to the research question. Of these five, four were women of colour and one a male student of colour studying engineering.Analysis led to the development of 3 Group Experiential themes: namely – ‘engineering identity’, ‘integration’ and the ‘impact of race and gender’. Overall, these themes demonstrated that childhood experiences helped to build an engineering identity and tolerance to white male culture. However, the oppression experienced in higher education was exacerbated by combined gender and race identity. Women of colour were exposed to a wide range of unchallenged sexualised attitudes and behaviour, often leading to feeling unsafe in the university environment. International students faced challenges to integration into university, British, and local cultures, presenting as a system of values, traditions, languages, policies, and practices, which were complex to navigate. The absence of role models in peers, or academics, to gain advice and support incited isolation and alienation in women of colour, impacting on their wellbeing, opportunities, performance, and aspiration.Together, the current study illuminated how socio-political factors and identity markers influence the student body and public and affect the experiences of being a woman of colour in higher education in the UK. Findings show the interconnections of race, gender, ethnic background, and world media influence the educational and social experience, and perception and choice of women of colour about whether to pursue an engineering career in the UK or generally.